Profil Industri Kerajinan Dulang dan Sumbangannya terhadap Pendapatan Total Rumah Tangga Petani di Desa Pengotan Kecamatan Bangli Kabupaten Bangli - NI LUH PUTU ERMA MERTANINGRUM; I WAYAN WIDYANTARA; A.A.A WULANDIRA SAWITRI DJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
ABSTRACT Dulang Craft Industry Profile and the Contributions Against Total Household Income of Framer in Pengotan village of Bangli District of Bangli Regency Pengotan village is a village that became the center of handicraft industry of household, one types of handicraft that produced in this village is the dulang craft. Dulang is one of the means that used as offerings at Hinduism ceremony. In addition, the survival dulang industry this is also useful as a medium inpreserving local culture. The purpose of this study is to find out how much acceptance of farmer household is; to determine how the labor productivity and productivity costs such; and to find out how big the contribution of dulang industry to total household income of farmers. Data analysis method that used in this study is the formula of acceptance, the labor productivity and costs productivity and the percentage contribution of the craft. The results showed that, the handicraft industry is able to provide additional income to the total income of the household, the level of labor productivity and costs productivity dulang craft industry can be classified as an i productive industrial because it has more value than one, and dulang craft workmanship able to providing a substansial contribution to earning total farm households. Keywords: Pengotan Village, Dulang Craft